Studies on Neotropical Phasmatodea XXV: Revision of Pterinoxylus Serville, 1838, with the descriptions of two new species from Costa Rica. (Phasmatodea: Oriophasmata: Cladomorphinae: Pterinoxylini) - Hennemann, Frank H.; Conle, Oskar V.; Valero, Pablo; Nishida, Kenji (Zootaxa, 2022)
The genus Pterinoxylus Serville, 1838 is redescribed and revised at the species level. It is distributed throughout most of Central America, the northern half of South America and also has one species on the Lesser Antilles. Detailed descriptions, notes on intraspecific variability and illustrations are provided for all six known species. Keys are presented to distinguish males, females and eggs. Two new species are described from Costa Rica: P. cocoense n. sp. from both sexes and the eggs and P. speciosus n. sp. from both sexes. The female of P. perarmatus (Redtenbacher, 1908) is described and illustrated for the first time, as are the eggs of the type-species P. eucnemis Serville, 1838 and P. perarmatus (Redtenbacher, 1908). The external morphology of all species shows considerable intraspecific variability, which is discussed and illustrated. While P. cocoense n. sp. is an endemic and the only stick insects that has so far become known from Cocos Island a small island some 550 km off the Costa Rican Pacific coast, all other species appear to have fairly wide distributional ranges. Maps show the distributions of all six known species. Type-specimens of the two newly described species are deposited in the collections of MNCR-A (Costa Rica) and Zoologisches Museum und Universität, Hamburg, Germany (ZMUH).